2019
DOI: 10.1093/jpids/piz094
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Associated Antibiotic Tolerance in Pediatric Clinical Isolates of Pseudomonas aeruginosa

Abstract: Background When grown in human serum, laboratory isolates of Pseudomonas aeruginosa exhibit tolerance to antibiotics at inhibitory concentrations. This phenomenon, known as serum-associated antibiotic tolerance (SAT), could lead to clinical treatment failure of pseudomonal infections. Our purpose in this study was to determine the prevalence and clinical impact of SAT in Pseudomonas isolates in hospitalized children. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
1
7
0
1
Order By: Relevance
“…On the other hand, the MBEC 80 of pre-formed P. aeruginosa biofilms grown in FBS and IVWM was determined to be 8 ​μg/mL, an 8-fold increase compared to LB. The presence of serum is known to increase antimicrobial tolerance [ [104] , [105] , [106] ], owing to the serum-binding properties of certain antibiotics, including binding of tobramycin and serum albumin [ 107 ]. However, this increased tolerance could also be due to the inherent biofilm properties under these conditions, including nutrient distribution and variations in microbial metabolism [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the MBEC 80 of pre-formed P. aeruginosa biofilms grown in FBS and IVWM was determined to be 8 ​μg/mL, an 8-fold increase compared to LB. The presence of serum is known to increase antimicrobial tolerance [ [104] , [105] , [106] ], owing to the serum-binding properties of certain antibiotics, including binding of tobramycin and serum albumin [ 107 ]. However, this increased tolerance could also be due to the inherent biofilm properties under these conditions, including nutrient distribution and variations in microbial metabolism [ 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, in zinc-depleted media, more analogous to human zinc concentrations, these organisms are more sensitive to carbapenems and better predict in vivo outcomes ( 40 ). Conversely, Morrison et al ( 41 ) demonstrated among respiratory and blood Pseudomona s aeruginosa isolates recovered from pediatric patients that some had lower aminoglycoside and minocycline MICs in traditional medium than in serum-based media. The impact of these newly identified conditional differences in MIC on the patient PK/PD response has not been identified, but this is an area of further interest to study.…”
Section: Pathogen Minimum Inhibitory Concentration and Its Impact On Tdmmentioning
confidence: 99%
“…On the other hand, the MBEC 80 of preformed P. aeruginosa biofilms grown in FBS and IVWM was determined to be 8 µg/mL, an 8-fold increase compared to LB. While the presence of serum is known to increase antimicrobial tolerance [101][102][103], owing to the serum-binding properties of certain antibiotics, including binding of tobramycin and serum albumin [104], this increased tolerance could also be due to the inherent properties of the biofilm formed under these conditions. The similarity of MBEC 80 in FBS and IVWM (which contains 70% FBS) could possibly indicate the dominant role of serum in influencing the antibiotic tolerance of P. aeruginosa biofilms.…”
Section: Antibiotic Susceptibility Of P Aeruginosa and S Aureus Biomentioning
confidence: 99%